A,The The Impact of Institutional and Village Cooperation Training on Enhancing the Capacity of Institutional - Sri Nuriyani; Sujarwo Sujarwo (Universitas Medan Area, 2025)
This qualitative evaluative study examines the effectiveness of institutional and inter-village cooperation training organized by the Village Government Training Center in Yogyakarta, Indonesia. The training was designed to strengthen village governance by Law No. 6/2014 on Villages. Data were collected through observations, in-depth interviews, and document analysis, involving organizers, facilitators, and participants selected via purposive sampling. The study employed the CIPPO model—Context, Input, Process, Product, Outcome—as the analytical framework, and data were analyzed using Miles, Huberman, and Saldaña’s interactive model. Findings show that the training addressed contextual needs and was delivered through participatory methods, enhancing participants’ understanding of institutional structures and encouraging initial follow-up actions such as cooperation drafts and business initiatives. Inputs such as curriculum content and facilitator quality were adequate, although limitations in digital infrastructure and training duration were identified. Participants demonstrated short-term behavioral changes and initiated inter-village collaborations, yet sustaining long-term outcomes remained a challenge. The study concludes that adaptive, needs-based training must be supported by systematic mentoring and monitoring to foster sustainable governance improvements. Practical implications include the need for integrated post-training support systems and digital learning innovations to align training with the broader goals of decentralization.